The INTERACT Institute: Observations on Dissemination of the INTERACT Quality Improvement Program Using Certified INTERACT Trainers. (6th November 2014) - Bonner, Alice; Tappen, Ruth; Herndon, Laurie; Ouslander, Joseph
Abstract: Unnecessary hospitalizations of vulnerable nursing home (NH) residents can lead to hospital-acquired conditions, morbidity, mortality, and excess health care expenditures. Previous research has shown that a substantial percentage of these hospitalizations are preventable. Interventions to reduce acute care transfers (INTERACT) is a quality improvement program that has been adopted by many NHs throughout the United States. The original INTERACT toolkit was first created in a project supported by the Centers for Medicare and Medicaid Services. The toolkit was further refined and tested in a collaborative quality improvement project involving 30 NHs in 3 states, which resulted in a 17% reduction in all-cause hospitalizations. This study was limited because it was not randomized or controlled. Nevertheless, the data provide evidence that the program, even in the absence of strong regulatory oversight or financial incentives, is feasible to implement and that more active program engagement is associated with higher reductions in hospitalization. This paper describes dissemination of the INTERACT program using a pragmatic and relatively low cost model to prepare certified INTERACT Trainers in collaboration with several professional organizations.